2021
DOI: 10.3389/fninf.2021.662967
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analysis of the Proteome in Exosomes Derived From Plasma: Exosomes Involved in Cholesterol Metabolism Process of Patients With Spinal Cord Injury in the Acute Phase

Abstract: Spinal cord injury (SCI) is a common but severe disease caused by traffic accidents. Coronary atherosclerotic heart disease (CHD) caused by dyslipidemia is known as the leading cause of death in patients with SCI. However, the quantitative analysis showed that the cholesterol and lipoprotein concentrations in peripheral blood (PB) did not change significantly within 48 h after SCI. Due to the presence of the Blood spinal cord barrier (BSCB), there are only few studies concerning the plasma cholesterol metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…These results suggest that plasma exosomes are involved in the regulation of lipid metabolism in the acute stage of spinal cord injury, and may be involved in the regulation of metabolic reprogramming of tissue microenvironments in other diseases. 26 In our study, we knocked down MMP1 in OLK-MSCs and Ca-MSCs using siRNA, and might have changed the other content of exosomes; more convincing evidence should be provided by either direct knockout exclusion of MMP1 or via MMP1-specific immune neutralization in exosomes. Future studies should focus on identifying the key downstream molecules and pathways to better understand the significance of exosomal MMP1 in preparing the precancerous and premetastatic niche.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These results suggest that plasma exosomes are involved in the regulation of lipid metabolism in the acute stage of spinal cord injury, and may be involved in the regulation of metabolic reprogramming of tissue microenvironments in other diseases. 26 In our study, we knocked down MMP1 in OLK-MSCs and Ca-MSCs using siRNA, and might have changed the other content of exosomes; more convincing evidence should be provided by either direct knockout exclusion of MMP1 or via MMP1-specific immune neutralization in exosomes. Future studies should focus on identifying the key downstream molecules and pathways to better understand the significance of exosomal MMP1 in preparing the precancerous and premetastatic niche.…”
Section: Discussionmentioning
confidence: 77%
“…For instance, studies have reported that APOB does not change significantly in the peripheral blood of patients with acute spinal cord injury, however, APOB expression in peripheral plasma exosomes increases significantly. These results suggest that plasma exosomes are involved in the regulation of lipid metabolism in the acute stage of spinal cord injury, and may be involved in the regulation of metabolic reprogramming of tissue microenvironments in other diseases 26 …”
Section: Discussionmentioning
confidence: 82%
“…This transport, however, can be mediated by exosomes, which were reported to carry nucleic acid and proteins across BBB [ 13 ]. The existence of ApoE in the human plasma exosomes has been also reported recently [ 14 ]. Vacuolar ATPases (V-ATPases) are ATP-dependent proton pumps, highly expressed in the ruffled border membranes to acidify the resorption lacunae [ 15 ].…”
Section: Introductionmentioning
confidence: 73%
“…Therefore, the mRNA HIST1H2BM in the above pathways might play a role in participating in lipid metabolism. Moreover, the downregulating protein HIST1H2BM was also found that may be involved in regulating lipid metabolism or other signaling pathways in the acute phase of spinal cord injury [ 38 ].…”
Section: Discussionmentioning
confidence: 99%